Efecto de diferentes dosis de NPK, como complemento de un abonamiento orgánico, en el cultivo de Brassica oleracea L. “coliflor”, var. Botrytis, hibrido snow white, en un suelo de baja fertilidad, Zungarococha, Loreto - Ramirez Buendia, Cherly Cecilia (2013)
The research was carried out in order to evaluate the manure by supplementing with doses of N P K in the fertilization of cauliflower. The statistical design of the study was the BCA and the Comparisons Test was Duncan's. The results of the study led to the following: The agronomic characteristics and yield of cauliflower were improved by the addition of NPK as a complement to organic fertilizer (manure). Treatments T4 (manure + 250-50-500) and T3 (chicken manure + 150-40-400) had a minimal difference. The yield of 10,250 kg of pella/ha respectively of the T4 treatment was higher. Manure manure (T1) produced a yield of 6,840 kg of pella /ha, being surpassed by Treatments T2 (poultry manure + 100-30-300) with 9,010 kg of poultry manure/ha, Treatment T3 (poultry manure + 150-40-400) with 10,170 kg of poultry manure/ha and Treatment T4 (poultry manure + 250-50-500) with 10,250 kg of poultry manure/ha. The best profitability was obtained in the T3 Treatment (150-40-400) with S/.18,224, surpassing the T4 Treatment (manure +250-50-500) with S/.17,733.